Probing the wave fronts based on autocorrelation - Han, Yujing; Ren, Shufeng (Journal of modern optics, 2010)
We proposed an easy method for probing the wave fronts via a typical Fourier transform system. An amplitude only spatial light modulator (SLM) was set on the front focal plane of a Fourier lens to control the wave front transmittance. A CCD was set on the back focal plane of the Fourier lens to record the intensity patterns. The Fourier transform of the intensity pattern is the autocorrelation of the wave front passing through the SLM. When we choose suitable pixels of the SLM to permit the wave front passing through, the information from the wave front illuminating the pixels can be directly extracted from the Fourier transform of the diffraction intensity pattern without complicated calculations. The complex amplitude of the wave front illuminated on the SLM can be probed using the above-mentioned method. The simulation results certifying our theory were also given.